Pengaruh Leverage, Firm Size, dan Free Cash Flow terhadap Dividend Policy dengan Profitability sebagai Variabel Mediasi - Yunia Andini; Menik Indrati (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
This study aims to analyze the effect of Leverage, Firm Size, Free Cash Flow on Dividend Policy with Profitability as a mediating variable. Dividend policy reflects the purpose of financial management in which the company manages fund income and allocates funds to achieve company value, namely shareholder prosperity share. The sampling technique used is a purposive sampling technique by establishing a number of criteria. In this study, there were 8 companies that met the criteria from a total observation of 73 companies with research objects in the property and real estate subsector companies listed on the Indonesia Stock Exchange (IDX) during the period 2016 to 2021. The data processing technique used was multiple linear regression with SPSS application assistance. The results of the study show that leverage, firm size, free cash flow and profitability have a simultaneous effect on dividend policy. Leverage has a negative effect on dividend policy. Firm size has no effect on dividend policy and free cash flow has a positive effect on dividend policy. Profitability does not moderate the effect of leverage and firm size on dividend policy, but positively mediates the effect of free cash flow on dividend policy.